2023
DOI: 10.1097/prs.0000000000010376
|View full text |Cite
|
Sign up to set email alerts
|

Laser combined with radiotherapy for keloid treatment: a novel and efficient comprehensive therapy with a lower recurrence rate

Abstract: With keloids, a fibroproliferative skin disorder characterized by gradually spreading skin involvement, patients not only have cosmetic disfigurement and functional impairment but also psychological burden. Available treatments include intralesional corticosteroid or 5-fluorouracil injection, surgical excision, laser therapy, radiotherapy, pressure therapy, and application of silicone gel. Despite the variety of available treatment methods, the recurrence rate remains high. 1 Laser is a fast-growing treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…22,23 In recent years, with the advancement of optoelectronic technology and a public focus on aesthetics, laser therapy has been widely used in clinical practice because of its advantages such as less trauma, faster recovery, and significant improvement in scar appearance. [24][25][26] Because of its low efficiency and high recurrence 95% CI: −1.17 to −0.63) were significantly improved after fractional CO 2 laser treatment for keloids, although vascularity did not significantly change. However, there was significant heterogeneity (I 2 = 98.0%, p = 0.000) in the analysis of vascularity, challenging the confidence in this aspect of our results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…22,23 In recent years, with the advancement of optoelectronic technology and a public focus on aesthetics, laser therapy has been widely used in clinical practice because of its advantages such as less trauma, faster recovery, and significant improvement in scar appearance. [24][25][26] Because of its low efficiency and high recurrence 95% CI: −1.17 to −0.63) were significantly improved after fractional CO 2 laser treatment for keloids, although vascularity did not significantly change. However, there was significant heterogeneity (I 2 = 98.0%, p = 0.000) in the analysis of vascularity, challenging the confidence in this aspect of our results.…”
Section: Discussionmentioning
confidence: 98%
“…However, laser‐assisted 5‐FU delivery tended to show a higher extent of improvement in scar characteristics than laser‐assisted verapamil hydrochloride delivery, without significance 25 . The latest study also found that fractional CO 2 laser combined with radiotherapy is a new comprehensive therapy composed of ablative lasers and radiotherapy for keloids with excellent clinical efficacy, low recurrence rate and no serious adverse effects 26 . Therefore, future studies will focus on exploring the efficacy and safety of fractional CO 2 laser combined with keloids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods include surgical excision, compression therapy, radiotherapy, topical silicone bands, silicone gels, intralesional injections (steroids, verapamil, bleomycin, 5-fluorouracil, botolinum toxin type A, platelet rich plasma), cryotherapy, and laser treatments. [4][5][6][7][8] When only surgical excision is performed, the recurrence rate varies between 45% and 100%. For this reason, keloid treatment is a very difficult process, and due to these high recurrence rates, it is recommended to use surgical treatment in combination with other methods as recurrence rates decrease when combined treatments are used.…”
mentioning
confidence: 99%